Memory: in my brain and beyond - Florence Tribolet (Cortica, 2023)
The brain is a complex organ of which we still do not know everything. Without any external stimulus, the brain can internally generate feelings, emotions, and thoughts itself, just by remembering (consciously or not). But it can also erase feelings, and thoughts to protect itself. Brain can create and destroy, which is quite powerful. Regarding memory, the same applies: our brain can create false memories, a big issue in testimony in court, and it can delate memories, when too traumatic or simply not relevant anymore. In this work, I will talk about memory in general, beginning with information on how the encoding process works in standard situations. I will continue by presenting what are the engrams and how a single memory is globally distributed in the whole brain. I will further present what is collective mind and how it shapes our own cognition. I will end with interesting philosophical questions (at least, for me) raised by these studies.